Djiboutian sovereignty: worlding global security networks. - Cobbett, Elizabeth; Mason, Ra (International Affairs, 2021)
The research problem this article addresses is whether the unique confluence of overseas security forces in a single territorial space through the leasing of land for foreign military bases compromises the state's sovereignty. We study Djibouti's practice of renting land to military powers from an analytical position that is diametrically opposed to the literature on the 'scramble' for Africa and often erroneous assumptions of an erosion of sovereignty. Using the concept of 'worlding', we argue in this article that instead of reading 'military base diplomacy' as eroding and undermining Djibouti's sovereignty, this case demonstrates the ways in which 'the art of being global' underpins new forms of territoriality and unexpected forms of locality in Africa. Consequently, we maintain that African experiences of sovereignty offer the challenges, along with the rewards, of greater analytical depth to International Relations scholarship while expanding our understanding of different empirical cases beyond the western-centric accounts of sovereignty in line with an abstract ideal that does not tell us much about the world, postcolonial experiences and global politics. Through a case-study approach, we focus specifically on the stark distinctions between Japan and China, which both have their respective first postwar overseas military bases in the country, and the Djiboutian state itself, in terms of how each are interpreting and practicing sovereignty to fit their own national narrative, international status and domestic legal frameworks. The findings challenge simplistic analyses of African states as victims of exploitative Great Powers, gradually and repeatedly being stripped of their sovereignty.